Evolution of the Gut Microbiome in Early Childhood: A Cross-Sectional Study of Chinese Children - Niu, Jing; Xu, Long; Qian, Yun; Sun, Zhuo; Yu, Dongbao; Huang, Jiandong; Zhou, Xiaolin; Wang, Yizhong; Zhang, Ting; Ren, Rongrong; Li, Zhengpeng; Yu, Jialin; et al. (Frontiers in Microbiology, 2020)
Temporal development of the human gut microbiome over early childhood is driven by a variety of factors. We surveyed the fecal microbiome of 729 Chinese children aged 0–36 months, aiming to identify the age-specific patterns of microbiota succession, and evaluate the impact of birth mode, gender, geographical location, and gastrointestinal tract symptoms on the shaping of the gut microbiome. We demonstrated that phylogenetic diversity of the gut microbiome increased gradually over time, which was accompanied by an increase in Bacteroidetes and a reduction in Proteobacteria species. At a community level, the succession from aerobic bacteria and anaerobic bacteria to facultative anaerobes, and from Gram-negative to Gram-positive species was found over the gut microbiota development. The metabolic functions of the gut microbiome shifted tremendously alongside early physiological development, including an increase in alanine, aspartate, and glutamate metabolism, and a reduction in glutathione, fatty acid, and tyrosine metabolism. During the first year of life, the Bacteroidetes phylum was less abundant in children born by caesarean section compared with those delivered vaginally. The Enterococcaceae family, a group of facultative anaerobic microorganisms with pathogenic potential was predominant in preterm infants. No measurable effect of maternal antibiotic exposure on gut microbiota development was found in the first three years of life. The relative abundances of Coriobacteriaceae and Streptococcaceae families, and Megasphaera genus were found to be higher in girls than in boys. Among the three first-tier Chinese cities, children born and fed in Beijing had a higher abundance of Enterococcaceae and Lachnospiraceae families, and Shenzhen children had a higher abundance of Fusobacteriaceae. The families Alcaligenaceae, Bacteroidaceae, and Porphyromonadaceae were more abundant in children with constipation, whereas the relative abundance of the Clostridium genus was higher in those with diarrhea.